1970
DOI: 10.1002/cne.901400307
|View full text |Cite
|
Sign up to set email alerts
|

Cells of origin of sympathetic pre‐ and postganglionic cardioacceleratory fibers in the pigeon

Abstract: The pre-and postganglionic cardioacceleratory innervation is described in the pigeon. The peripheral coursc of the postganglionic cardiac nerves has been determined using microdissection and electrical stimulation. Using these techniques and retrograde degeneration methods, the distribution within the sympathetic ganglia of the cells of origin of these fibers has been localized to the three right caudal cervical ganglia (12, 13 and 14). It has also been shown o n the basis of electrical stimulation combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

1970
1970
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…This may be related to functional differences between the right and left sympathetic cardiac nerves. In the pigeon, electrical stimulation of the right cardiac nerve consistently increases heart rate, whereas this is not true for the left [20]. In parasympathetic and sensory innervation to the heart of the duck, we could not detect obvious laterality.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…This may be related to functional differences between the right and left sympathetic cardiac nerves. In the pigeon, electrical stimulation of the right cardiac nerve consistently increases heart rate, whereas this is not true for the left [20]. In parasympathetic and sensory innervation to the heart of the duck, we could not detect obvious laterality.…”
Section: Discussioncontrasting
confidence: 64%
“…In the present study, however, sympathetic postganglionic neurons innervating the heart were observed in the paravertebral ganglia C15 to T3, especially in the ganglion T1. After transection of the sympathetic cardiac nerve in the pigeon, chromatolytic neurons were observed in the paravertebral ganglia C12 to C14 and the proportion of such cells was highest in the ganglion C14, intermediate in the ganglion C13 and lowest in the ganglion C12 [20]. Moreover, HRP-labeled neurons were found in the paravertebral ganglion C14 following application of HRP to the sympathetic cardiac nerve of the pigeon [3].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The last cervical segment, all thoracic segments, and the first two lumbar segments contain preganglionic neurons of the sympathetic nervous system. Caudal to the lumbosacral enlargement there are preganglionic neurons of the parasympathetic system (Terni 1923;Huber 1936;MacDonald and Cohen 1970;Ohmori et al 1984;Hosoya et al 1992). All studies in avian species agree that preganglionic autonomic neurons are localized in a welldefined intermediomedial cell column dorsal to the central canal, the column of Terni (CT).…”
Section: Intermediate Regionmentioning
confidence: 55%
“…The medial ones, which also receive projections as a result of the same medullary injection, and therefore possibly from the same neurons, extend into the column of Terni. Since preganglionic neurons for the heart are located in the column of Terni at upper thoracic levels (Macdonald and Cohen, 1970;Cohen, 1977a, 1977b), it is possible that the descending axons mediate influences upon both the cardiac and respiratory systems, an arrangement possibly conducive to cardio-respiratory integration. The column of Terni is also known to receive projections from the raphe nucleus (Cabot et al, 1979), which probably accounts for the presence of retrogradely labeled cells in the raphe following spinal injections in the present study.…”
Section: Motoneurons Innervating Inspiratory Musclesmentioning
confidence: 99%